Posthuman Creativities: Pluralist Ecologies and the Question of How. (June 2022) - Harris, Daniel X.; Rousell, David
This editorial lays the groundwork and context for this special issue addressing a range of posthuman ecological approaches to the study and theorization of creativity, and its potential to transform understandings of 21st-century learning events and environments, including cities, schools, museums, parklands, digital environments, wild places, and more. Importantly, this collection establishes an ethics and politics of posthumanism as it intersects with creativity, including attention to the necessity and ethics of the ways in which Indigenous knowing and knowledge creation are changing and expanding traditional academic framings of arts-based research, creativity, and posthuman scholarship.